Optical absorption on exciton states in nanosystems with germanium quantum dots - Serhii I. Pokutnii (Chemical Physics Impact)
A theory of optical absorption on surface exciton states with spatially separated electrons and holes has been developed (the hole moves in a germanium quantum dot, and the electron is localized at the spherical interface of the silicon quantum dot matrix). A gigantic increase in polarizabilities (by five orders of magnitude) and absorption cross- sections (by eleven orders of magnitude) due to optical interband transitions between these exciton states has been theoretically predicted. This opens up the possibility of applied nanosystems as new highly absorbing nanomaterials in the infrared range.